Microwave Irradiated Rice Husk Based Activated Carbon For Adsorption Of Chloramphenicol - Mohd Shah, Izlan (Universiti Sains Malaysia, 2021)
Pharmaceutical industry was one of the main contributors of Chloramphenicol (CAP) to the water sources which can causes various environmental problems. In recent years, agriculture waste based activated carbon has been employed as an adsorbent in the treatment of antibiotics wastewater. The purpose of this study is to investigate the performance of activated carbon (AC) generated from rice husk (RH) for the removal of Chloramphenicol (CAP) by physical activation utilizing carbon dioxide (CO2) gasification and microwave irradiation technique. Response Surface Methodology (RSM) was used to optimize the rice husk based activated carbon’s (RHAC) preparation parameters of radiation power and activation time for adsorption of Chloramphenicol (CAP). The optimum conditions for RHAC preparation were observed to be 490 W of radiation power and 2 minutes of activation time which resulted 92.15% of CAP removal and 65.43% of RHAC’s yield. The CAP adsorption by RHAC increased as the initial CAP concentration and contact time increased. Adsorption equilibrium of CAP onto RHAC followed Freundlich isotherm. The kinetic studies of CAP adsorption onto RHAC was best represented by pseudo-second order kinetic models. According to the thermodynamic analysis, the value of ∆H° was negative, indicating that the adsorption was an exothermic process.